PHARMACOKINETIC PROFILE AND COMPARATIVE BIOAVAILABILITY OF PENTOXYPHYLLINE FROM TWO SUSTAINED-RELEASE PENTOXYPHYLLINE TABLETS IN INDONESIAN HEALTHY VOLUNTEERS - Yeyet C. Sumirtapura; Wibawati Sulistyo; Herwanto Suhalim (Indonesian Journal of Pharmacy, 2003)
In order to assess the quality of a sustained-release pentoxyphylline tablet formulated and produced by a domestic company (PLTF-400), a comparative bioavailability study was carried out in twelve healthy Indonesian volunteers in two-way crossover design. TRTL-400, innovator's product, was taken as reference product. Plasma sample was used and unchanged pentoxyphylline compound was analyzed using HPLC method. It was found that PLTF-400 was bioequivalent to the reference product (TRTL-400) with 90 % confidence intervals of Cmax, AUC0-t and AUC0- ratio (Test/Reference) of 93.1%-132.0%, 90.6% - 123.5%, and 84.2% - 116.2%, respectively. The pharmacokinetic parameters (Cmax, AUC, half-life) of the drug found in this study were comparable to those obtained previously by the other authors in differrent ethnics.Keywords: Pentoxyphylline, sustained-release, bioavailability, pharmacokinetics.